COMPARATIVE ANALYSIS OF MODERN TECHNOLOGIES IN SMALL-SCALE EDUCATIONAL INSTITUTIONS IN POLAND AND UKRAINE (EARLY XXI CENTURY) - Prokopiv, Liubov (Mountain School of Ukrainian Carpaty, 2023)
The development of modern education in Ukrainian rural small schools is an urgent and important issue in the context of the formation of the educational system in Ukraine. The systematic closure of such schools, low birth rates, and the demographic crisis pose serious challenges to providing accessible education in rural areas. A comparative analysis with the experience of Poland, where a similar situation exists, will allow us to identify opportunities to use foreign experience and develop positive practices for Ukrainian education. The purpose of this article is to highlight the specifics of small schools in Poland and Ukraine. The article aims to analyze the problem of preserving and developing such schools in both countries, as well as to identify opportunities to use foreign experience to improve the conditions of education and upbringing of Ukrainian youth. To achieve this goal, the methods of comparative analysis, analysis of the legislative framework and statistical data were used. The results of the study show that Ukraine and Poland have similar problems in preserving small rural schools. The closure of such schools is due to low birth rates, the demographic crisis, and lack of funding. Some regions in Ukraine are taking steps to preserve rural schools, but this problem remains urgent. In the context of the Polish experience, as the practice of other countries shows, new approaches to understanding educational technologies and teaching methods in small rural schools can be found. That is why the experience gained in Poland is of great importance for Ukrainian education. The results of the study emphasize the need to study and adapt foreign experience to improve the situation in Ukrainian small rural schools.